Chronic complications of diabetes mellitus related to the respiratory system - Zuzana Michnová; Miriam Čiljaková; Jarmila Vojtková (Termedia Publishing House, 2012)
The quality of life in patients with diabetes mellitus is mainly determined by chronic diabetic complications which may affect all organ tissues including respiratory system. Microangiopathy of pulmonary capillaries, autonomic neuropathy, myopathy of respiratory muscles or changes in collagen belong to supposed pathophysiological pathways. This paper brings brief review about reported functional consequences in subjects with diabetes - decreased vital lung capacity and pulmonary volumes, decreased diffuse lung capacity for carbon monoxide, lower basal bronchial tone, lower cough reflex sensitivity, increased incidence of sleep obstructive apnea, increase in respiratory infections, disorders in respiratory muscles or phrenical nerve. Examination of pulmonary functions may serve for early detection of chronic complications in patients with diabetes.